Stakeholder Analysis on PAL 16 Tourism Development in Cikole Village - Riswandha Risang Aji; Visilya Faniza (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
Tourism is a sector that is well-developed in Greater Bandung. One of the places that has potential for tourism is PAL 16 in Cikole Village, this research article presents a stakeholder analysis conducted to assess the development of tourism in Cikole Village, while also examining the impacts of tourism on the village itself. The study adopts a qualitative research method, utilizing stakeholder analysis and descriptive analysis as the primary research techniques. This research uses in-depth interview as data collection method for primary data. The research stages are data collection, data analysis, and conclusion drawing. The research findings highlight the key stakeholders involved in the tourism development process, which include the village government, community, academics, and tourists. The analysis underscores the importance of collaboration among these stakeholders to effectively develop tourism in Cikole Village. Furthermore, the study reveals that tourism in PAL 16 has had positive impacts on the economic, social, and environmental aspects of the village. Economically, tourism has created new business opportunities, stimulated the local economy, and generated income for the local community. Socially, it has fostered cultural exchange, promoted community engagement, and enhanced local pride. Environmentally, tourism development has encouraged conservation efforts, raised awareness about natural resources, and supported sustainable practices. This research contributes to the understanding of stakeholder dynamics in tourism development and emphasizes the need for coordinated efforts among stakeholders to maximize the benefits and minimize the negative impacts. The findings provide valuable insights for policymakers, local communities, academics, and other stakeholders involved in the sustainable development of tourism destinations.